Scholarly publishing’s hidden diversity: How exclusive databases sustain the oligopoly of academic publishers - Simon van Bellen; Juan Pablo Alperin; Vincent Larivière (PLoS ONE, 2025)
Global scholarly publishing has been dominated by a small number of publishers for several decades. This paper revisits the data on corporate control of scholarly publishing by analyzing the relative shares of scholarly journals and articles published by the major publishers and the “long tail” of smaller, independent publishers, using Dimensions and Web of Science (WoS). The reduction of expenses for printing and distribution and the availability of open-source journal management tools may have contributed to the emergence of small publishers, while recently developed inclusive databases may allow for the study of these. Dimensions’ inclusive indexing revealed the number of scholarly journals and articles published by smaller publishers has been growing rapidly, especially since the onset of large-scale online publishing around 2000, resulting in a higher share of articles from smaller publishers. In parallel, WoS shows increasing concentration within a few corporate publishers. For the 1980–2021 period, we retrieved 32% more articles from Dimensions compared to the more selective WoS. Dimensions’ data showed the expansion of small publishers was most pronounced in the Social Sciences and the Arts and Humanities, but a similar trend is observed in the Natural Sciences and Engineering, and the Health Sciences. A major geographical divergence is also revealed, with English-speaking countries and/or those located in northwestern Europe relying heavily on major publishers for the dissemination of their research, while the rest of the world being relatively independent of the oligopoly. Finally, independent journals publish more often in open access in general, and in Diamond open access in particular. We conclude that enhanced indexing and visibility of recently created, independent journals may favour their growth and stimulate global scholarly bibliodiversity.